Optimizing impedance matching by a dual-carbon Co-regulation strategy of Co3O4@rGO/celery stalks derived carbon composites for excellent microwave absorption. (10th January 2023) - Xie, Xiubo; Wang, Yukun; Sun, Xueqin; Wang, Heshan; Yu, Ronghai; Du, Wei; Wu, Hongjing
Highlights: Co3 O4 @rGO/CDC composites with different mass ratios of rGO:CDC were prepared. S13 (weight ratio for rGO:CDC is 1:3) composite showed best microwave absorption performance. It showed RLmin value of -84.3dB and the widest effective bandwidth of 4.5 GHz. Better impedance matching can be obtained by tuning the CDC ratio. Abstract: Both macroscopic composition and microstructure should be considered for reasonable microwave absorbent designing. In this study, Co3 O4 @reduced graphene oxide (rGO)/Celery stalks derived carbon (CDC) was prepared by loading Co3 O4 particles into rGO and biomass-derived carbon mixture through oxidation precipitation. By changing the mass ratio of rGO to CDC, the dielectric and impedance matching properties of the composites can be easily regulated. The RLmin value of Co3 O4 @rGO/CDC13 composite (weight ratio for rGO:CDC is 1:3) reaches –84.3 dB with a thickness of 4.6 mm, and the widest effective bandwidth can be obtained at 4.5 GHz with a matching thickness of 2.8 mm. The Co3 O4 @rGO/CDC13 composite with multiple components (Co3 O4, CDC, rGO) and 3D net structure produces magnetic/dielectric loss combinations, interfacial polarization, and multiple reflections and scattering, and the CDC with half tube and half sheet structure is conducive to the optimization of impedance matching. The strategy of co-regulating dielectric properties of materials with double carbon provides a novel pathway for the preparation of lightweight, low-cost, and high-performance absorbers. Graphical abstract: Image, graphical abstract